2020
DOI: 10.3390/antibiotics9040145
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Alleviates Endotoxemia with Decreased Serum Levels of Soluble CD163 and Mannose Receptor and Partial Modification of Gut Microbiota in Cirrhotic Patients

Abstract: Rifaximin is a poorly absorbable antibiotic against hepatic encephalopathy (HE). This observational study aimed to elucidate the effect of rifaximin on intestinal permeability and gut microbiota in patients with decompensated cirrhosis. Thirty patients with decompensated cirrhosis were assessed by ammonia level, neuropsychological testing, endotoxin activity (EA), and serum proinflammatory cytokines at baseline and after four weeks of rifaximin treatment (1200 mg/day). Intestinal permeability was indicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Kaji et al reported that rifaximin decreased circulatory endotoxin levels through improvement of intestinal hyperpermeability, 26 suggesting that long-term rifaximin treatment could improve liver function. In the present study, however, liver function tests, except for serum ammonia levels, did not improve significantly during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Kaji et al reported that rifaximin decreased circulatory endotoxin levels through improvement of intestinal hyperpermeability, 26 suggesting that long-term rifaximin treatment could improve liver function. In the present study, however, liver function tests, except for serum ammonia levels, did not improve significantly during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Currently, norfloxacin and rifaximin are the forms of selective intestinal decontamination for which there is the most evidence in cirrhosis. [37][38][39] However, the major drawback of routine antibiotic prophylaxis is the emergence of multidrug-resistant organisms. 34 Thus, novel therapies have been proposed based on their ability to modify the altered intestinal microbiota such as probiotics and prebiotics, 19,[40][41][42][43][44][45] fecal microbiota transplantation, 46,47 phage therapy, 31 among others.…”
Section: Intestinal Dysbiosismentioning
confidence: 99%
“…The development and validation of antimicrobials also encompass the evaluation of their in vivo efficacy and side effects. In the paper of Kaji et al, the effects of rifaximin on the gut microbiome were investigated [18]. Rifaximin is an antibiotic used to hepatic encephalopathy, a disease comprising a wide range of neurological and psychiatric manifestations [18].…”
mentioning
confidence: 99%
“…In the paper of Kaji et al, the effects of rifaximin on the gut microbiome were investigated [18]. Rifaximin is an antibiotic used to hepatic encephalopathy, a disease comprising a wide range of neurological and psychiatric manifestations [18]. The study was based on 16S rRNA gene sequencing to assess alterations in the microbiota of fecal samples from 30 patients before and after rifaximin treatment [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation